A Test of the OPEC Cartel Hypothesis, 1974-1983: Discussion - Castanias, Richard P. (Journal of Finance, 1985)
Richard P. Castanias, A Test of the OPEC Cartel Hypothesis, 1974-1983: Discussion, The Journal of Finance, Vol. 40, No. 3, Papers and Proceedings of the Forty-Third Annual Meeting American Finance Association, Dallas, Texas, December 28-30, 1984 (Jul., 1985), pp. 1006-1008